Tantangan dan Hambatan Lembaga Perlindungan Saksi dan Korban (LPSK) Dalam Melaksanakan Tugasnya Di Kota Kupang - Maria Johania Novianti Laack; Heryanto Amalo; Sigit Prabowo Sonbait (Artemis Law Journal, 2026)
The Witness and Victim Protection Agency (LPSK) has a role in the criminal justice system, especially in providing protection and assistance to witnesses and victims. This study aims to identify the challenges and obstacles faced by witness and victim protection institutions in carrying out their duties and to determine the efforts of witness and victim protection insititutions in overcoming the challenges and obstacles in carrying out their duties.The approach method used in this study is descriptive research with an indepth interview method with representatives of the Witness and Victim Protection Agency (LPSK) in Kupang City. This study explores various aspects that influence the effectiveness of the performance of the Witness and Victim Protection Agency (LPSK). The results of the study indicate that the main challengs faced by the Witness and Victim Protection Agency (LPSK) include limited budget or funds from the Witness and Victim Protection Agency (LPSK) available so that it affects professionsls in carrying out their duties and in handing cases there is a lack of personnel or Human Resources (HARI). The challenges and obstactels faced by the Witness and Victim Protection Agency (LPSK) in carrying out its duties in Kupang City indicate the need to actively increase publik awareness in supporting the protection of witnesses and victims, increase socialization and public understanding of the role and function of the witnesses and Victim Protection Agency (LPSK) and resources to optimize protection and recovery for witnesses and victims of criminal acts in the area.